PERLINDUNGAN ANAK DARI TINDAK KEKERASAN SEKSUAL DI INDONESIA BERDASARKAN UNCRC 1989: The Protection of Children from Sexual Violence in Indonesia Based on the UNCRC 1989 - Tierza Prameswari Sudiono; Sujatmoko, Andrey (Reformasi Hukum Trisakti, 2025)
Cases of sexual violence in Indonesia continue to increase every year, the victims are now no longer teenagers and adults, but also now include children. This can directly or indirectly endanger the health, survival, dignity and development of children. Meanwhile, Indonesia has ratified the UNCRC of 1989, which guarantees children's rights in the civil, political, economic, social, health, and cultural domains. The formulation of the problem of this article is how is the protection of child victims of sexual violence in Indonesia based on the UNCRC 1989. This article uses normative research methods, is descriptive analytical, deductive inference, and is a literature study. The results and conclusion of the research are the forms of protection of child victims of sexual violence, among others, through legal instruments, implemented by a number of state institutions LPSK, Komnas Anak, and PPPA. The UNCRC 1989 in principle regulates the right to life, the right to health, the right to education, and the right to growth and development of children requiring the Indonesian state to take the necessary steps to protect children from all forms of sexual violence.